Analysis of Defects on PCB Using X - Plane Method - Mlýnek, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Using x – ray is one way for analyzing structural defects on PCB and lead components. X – Plane method is based on making individual 2D slices within a sample from top to bottom, front to back and left to right. There is no need to cut or destroy sample. X – Plane method works at high magnification. Method is showing position and size of voids or cracks, identifying head on pillow, open joint and other defects.
Keywords: X – plane; X – ray; defect; analysis